An Investigation Into The Propulsive Force Generation Of Multiple Flapping Surfaces - Mabvuu, Never (University of the Witwatersrand, Johannesburg, 2024)
The aerodynamic performance of flapping NACA0012 airfoils was analyzed through numerical simulation, focusing on the effects of stagger, gap, phase difference, and the number of airfoils. The simulation was conducted under specific conditions: 𝑈∞ = 0.2𝑚/𝑠, f=2Hz, 𝛼0=200, C=0.04m, St=0.2 and Re= 8000). The problem was modeled in ANSYS Fluent using a transient viscous approach with absolute velocity formulation, employing the pressure-based coupled solver (PBCS). PRESTO! interpolation and second-order upwind discretization were applied for pressure, momentum, intermittency, turbulent kinetic energy, and specific dissipation rate. Mesh validation and independence studies confirmed that the results were driven by the physics setup, independent of mesh configuration. It was discovered that small stagger and gap at φ=1800 is not good for thrust production as the airfoils produced thrust less than a single airfoil with ∆Ctav = -0.94. However, lift production is increased and ∆Clav =1.2. At larger spacing ∆Ct, ∆Cl and η generally become constant. One of the worst performing cases (X=1.0C;Y=0.5C; ϕ= 1800 ) was improved by making the aft airfoil lead ( φ= -450 ). This explains why insects alter φ or frequency depending on the situation and flight requirements. The most effective X-Y- ϕ were found to be the ones at which flow separation is suppressed. For the 4 airfoils cases the fore pair performed better than the aft pair for the small spacing case. When spacing was increased the aft pair performed better than the aft pair.
A research report submitted in fulfillment of the requirements for the Masters in Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Flapping; stagger and gap; Lift; Thrust; Performance index; phase angle; vorticity CFD; numerical simulation; SDG-17: Partnerships for the goals